'The problem-centred expert interview'. Combining qualitative interviewing approaches for investigating implicit expert knowledge. Issue 3 (4th May 2021) - Döringer, Stefanie
ABSTRACT: Expert interviews are a widely-used qualitative interview method often aiming at gaining information about or exploring a specific field of action. This paper wants to move beyond the focus on explicit expert knowledge by emphasizing the experts' individual perspectives that affect social practices in a field of action. The paper addresses the investigation of this implicit, interpretative expert knowledge by developing the 'problem-centred expert interview'. This approach merges the theory-generating expert interview that discusses the social relevance of expert knowledge and the problem-centred interview (PCI) that offers a dialogic-discursive interview procedure investigating individual perspectives. By drawing upon an empirical study in human geography, the paper demonstrates how one could conduct and analyse this methodical combination in research practice. The following discussion shows that, despite some pitfalls, the combination appears fruitful for divulging implicit expert knowledge and understanding the inner logics of decision-making processes. The paper concludes with an outlook on possible fields of application.